Solar Energy, Power Generation and Desalination Systerms - Kalogirou, Soteris A. (My University, 2012)
This chapter initially examines the interaction between energy related problems and the role of renewables in helping to reduce the impact of those problems. These are analyzed in terms of the energy demand and on the factors affecting it, then energy generated environmental problems are investigated in view of sustainable development. This is followed by an examination of the water demand and consumption, the relation of water and energy, the energy related to desalination and how renewables can be used to reduce associated risks. As the chapter deals with power generation and desalination, the hightemperature solar collectors that can be employed in these systems are presented which include the parabolic trough, Fresnel, parabolic dish reflector and heliostat field collectors. Subsequently, power generation and industrial process heat systems are presented which include the high-temperature collector systems as well as solar ponds, which are low temperature systems. In industrial process heat systems the basic concepts are presented as well as the solar industrial steam generation systems. The final section of this chapter presents the direct and indirect desalination systems. The direct systems refer to desalination units that collect the solar energy and produce fresh water in one piece of equipment whereas in the indirect systems two such sub-systems are employed, one for solar energy collection and one for desalination. The desalination systems presented under the indirect systems include the multi-stage flash process, the multiple-effect distillation process, the vapor compression process, reverse osmosis and electrodialysis. The first three belong to the vapor or phase change processes whereas the last two belong to the membrane processes. In all cases the way renewables can be used to power the desalination systems are indicated.
Keywords: Energy problems; Concentrating collectors; Concentrating solar power; Industrial process heat; Desalination; Direct collection systems; Indirect collection systems